Delivering mindfulness in the classroom via a technology-enabled approach: Feasibility and the potential impact on teachers' psychological well-being, self-efficacy, and mindfulness. (February 2023) - Klusmann, Birte; Sanderman, Robbert; Schroevers, Maya J.
Abstract: This longitudinal study included 64 teachers. We examined the feasibility and preliminary effects of a newly designed program, playing pre-recorded mindfulness practices to elementary school students by teachers across one school year. Self-report surveys and logbooks were used to collect data quantitative and qualitative data. During the first four months of implementation, teachers reported significant improvements in self-efficacy in classroom management and lower levels of perceived stress. Levels of mindfulness increased significantly and gradually throughout the school year. Qualitative results underlined potential changes in teachers' outcomes, suggesting a calming effect and perceived improvement in their teaching skills.